The Effect of Electric Stimulation Using Proposed Apparatus on Static Balance Through Hamstring Muscle Rehabilitating in Athletes Suffering from Mild Muscle Tear - Ismaeil, Karam Salam; Jawad, Baydaa Razzaq (Journal of Physical Education, 2023)
The problem of the research lies in the frequent injuries related to this muscle especially mild muscular tear in some hamstring muscles. The research aimed at identifying the effect of electric stimulation using proposed apparatuses on static balance through rehabilitating hamstring muscle in athletes suffering from mild muscular tear. The subjects were individual and team sport athletes suffering from muscular tear from 10/11/2022 till 10/3/2023. The researchers used the experimental method and the data was collected and treated using SPSS to conclude that electric stimulation have a positive effect on rehabilitating athletes with raptured hamstring. Finally, the researchers recommended applying the prospered program for rehabilitating other injured hamstring muscles.